Complexidade da farmacoterapia: perfil farmacoterapêutico e desfechos associados - Conceição, Vanessa Alves da (2018)
Introduction. Aging favors the appearance of propitious clinical conditions to a high use of medicines, a reality in the elderly over 65 years of age. However, the number of medicines used should not be the only predictor of a medication regimen complexity, other factors may increase the complexity of pharmacotherapy leading to possible problems related to pharmacotherapy. In this perspective, there are few national studies that evaluate the medication regimen complexity in the elderly, especially those that evaluate outcomes influenced by this complexity, so as to allow interventions for its optimization. Thus, the objective of this dissertation was to evaluate the pharmacotherapeutic profile and the health outcomes associated with the medication regimen complexity. Methods. This study was carried out in two stages. In the first stage, a descriptive cross-sectional study was performed to evaluate the medication regimen complexity of elderly patients in three long-term care facilities using the Medication Regimen Complexity Index (MRCI). This study was conducted for 12 months in three long-term care facilities in the state of Sergipe. In the second stage, a systematic review was performed to identify in the literature which outcomes were influenced by the medication regimen complexity, using the MRCI. We analyzed all study designs published until February 2017 who met the following eligibility criteria: using the MRCI instrument to measure the medication regimen complexity, assessing the medication regimen complexity for global regimens, related the medication regimen complexity with clinical and/or humanistic and/or economic outcome, was written in English, Spanish or Portuguese. Results. In the first stage, the evaluation of the medication regimen complexity obtained an average of 15.1 points (± 9.8), with a minimum of two and a maximum of 59 points. The highest levels of complexity were associated with the dose frequency, with a mean of 5.5 (± 3.6) points. A significant relationship between the medication regimen complexity and the variables polypharmacy, drug interaction, drug potentially inappropriate for the elderly and therapeutic duplicity was found (p <0.001). In the second stage, of the 610 studies evaluated, 20 met the eligibility criteria. The health outcomes most influenced by the medication regimen complexity were the clinical outcomes: hospitalization, hospital readmission and adherence to pharmacotherapy, most of the studies presented satisfactory results to association the outcomes with the complexity and obtained good methodological quality. Conclusion. This dissertation made it possible to evaluate the pharmacotherapeutic profile of elderly patients, showed that besides polypharmacy, potential drug interaction, therapeutic duplicity and potentially inappropriate medicines for the elderly are risk factors for the increased medication regimen complexity in these patients. Furthermore, identified that the health outcomes most influenced by the medication regimen complexity were ones clinical: hospitalization, hospital readmission and adherence to the pharmacotherapy.